Kemasan Cerdas Produk Talas Dusun Nenas: Meningkatkan Daya Saing dan Nilai Jual - Awaludin, Rizky; Mayasari, Endah; Wijaya, Hendry; Riakbar, Bima; Sapitri, Widia; Aulia, Virsha (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This community service and research aims to improve the welfare of farmers in Dusun Nenas, Dusun Nenas, Wajok Hilir Village, Kab. Mempawah, Prov. West Kalimantan, where most of the people depend on the agricultural sector. Taro, as one of the local commodities that has great potential, is rich in nutrients and has a unique flavor. However, the development of processed taro products by local MSMEs is constrained by less attractive and informative packaging. Effective packaging is essential to protect the product while attracting consumer attention. By utilizing the advantages of fresh and quality local raw materials, processed taro products have the opportunity to compete in the market. This research made efforts through training and mentoring in innovative packaging design to improve product competitiveness. This training is expected to help the community in creating more attractive and functional packaging, so as to increase the selling value of the product and strengthen its position in the market. It is expected that this activity will improve the quality of processed taro products, expand market reach, and make a positive contribution to the welfare of the community in Nenas Hamlet.